Linking Categories of Syntactic Units and Their Meaning in the Formation of Word Combinations - Khujanazarova Gulbakhor Gofurjanovna (Genius Journals, 2022)
The article discusses the categories that connect syntactic units and their importance. The aim of the work is to study the national and cultural features of English phrases, to reveal their general and specific aspects, and thus to further develop the theory of private, comparative and universal phrases.
Keywords: Phrases; English; combination; morphological